ANALISIS KEKUATAN HUKUM PERJANJIAN LISAN ARISAN ONLINE YANG MENGGUNAKAN MEDIA APLIKASI FACEBOOK MESSENGER DALAM PEMBUKTIAN DI PENGADILAN DITINJAU DARI UNDANG- UNDANG INFORMASI DAN TEKNOLOGI ELEKTRONIK NOMOR 11 TAHUN 2008 (STUDI KASUS PUTUSAN NO. 106/PDT.G/2017/PN.PLK) - Lidya Puspita; Ariawan Gunadi (Jurnal Hukum Adigama, 2019)
Oral Agreement in verdict number 106 / pdt.g / 2017 / pn.plk explain concerning the matter between Ahinny as a plaintiff and Lucia as one of a defendant . These problems starts with mutual agreement do online social gathering  that contained in facebook messenger, When the defendant won the online social gathering , the defendant as participant of that would no longer make the online social gathering contributions they were due to pay. The methodology of the research is normative method. The problem arises in this research is how the legal force of oral online social gathering  that using media application facebook messenger in proof in court in terms of the law of information and technology electronic number 11 years 2008. The online arisan oral agreement in this case is an oral agreement with mutual trust between one another and will give rise to rights and obligations among the participants. This agreement will have legal force if the parties have agreed to hold an arisan with a value of money or certain goods and within a certain period of time, then actually an agreement has occurred among the participants of the social gathering. Facebook is intermediary and Facebook is not a responsible for disputes or defaults that occur between the online arisan parties. Based on technological advances and the rapid development of information techniques, the Government should immediately recognize that electronic evidence must be recognized and used as evidence in court.